Potential Molecular Interaction of Nutmeg’s (Myristica fragrans) Active Compound via Activation of Caspase-3 - Ronny Lesmana; Filza Yulina Ade; Yuni Susanti Pratiwi; Hanna Goeanawan; Nova Sylviana; Sandra Megantara; Susianti Susianti; Vita Murniati Tarawan; Purwo Sri Rejeki; Hamidie Ronald Daniel Ray; Unang Supratman (Universitas Pendidikan Indonesia, 2022)
Myristica fragrans Houtt (belongs to the Myristicaceae family) is a Maluku Island (Indonesia) native plant. The seed of M. fragrans (Nutmeg) has been used for medicinal benefits. M. fragrans also has anti-cancer properties. The goal of this research was to use computer-aided drug design to investigate the in silico molecular docking of selected nutmeg compounds against Caspase-3. Molecular docking using Malegro Virtual Docker (MVD) software Ver 5.5 was performed to investigate binding complicated models to offer information on critical drug-receptor interactions. The most potent ligand was Licarin B, which had a docking score of -103.07 kcal/mol. The Licarin B structure formed several hydrogen bonds with Trp214 and Phe250. These findings imply that the nutmeg seed contains a prospective compound that could be a great anti-cancer agent.